Akses Keadilan Bagi Perempuan Dan Pidana Anak Dalam Pembangunan Berkelanjutan - Nur Hidayati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research examines the world's commitment to overcoming the problem of violence against women and children which is specifically stated in the sustainable development goals (sustainable development goals), including Indonesia. This type of research is normative juridical law, namely explaining and analyzing sexual violence experienced more by women and children. The approach method uses the statute approach by analyzing legislation in the form of Prosecutor's Guidelines No. 1 of 2021, Law no. 23 of 2004, Law No.17 of 2016 and PERMA No. 3 of 2017 as primary legal material. Secondary legal materials include publications on law including textbooks, journals and the Criminal Code. The legal material analysis technique is a method of grammatical and systematic interpretation. The results of the study show that there is an SPPT-PKKTP, women have the right to get justice for ongoing legal efforts, self-recovery for deprivation of rights and violence they experience, children's rights in the criminal justice process are regulated separately, namely in Article 3 of Law No.11 of 2012 regarding the Juvenile Criminal Justice System (UU SPPA). This research is expected to enrich the discourse towards renewal and development of criminal law in the future or as a reference for subsequent studies.